2018
DOI: 10.3390/su10082677
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Internet Entrepreneurs’ Social Network Behaviors and Entrepreneurship Financing Performance

Abstract: From the perspective of social network behavior, our paper discusses the relationship between agricultural entrepreneurial social network behavior and entrepreneurial financing performance in an Internet crowdfunding setting, and investigates the moderating role of entrepreneurial team size. In this paper, the data-mining method is used to capture and collate data regarding 7585 venture projects on an Internet crowdfunding platform between 2014 and 2017. Ordinary least squares (OLS) and Probit models are appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Furthermore, the break-down of traditional and hierarchical structures also talks about organizational-wide communications that enable the expansion of a shared revelation (Hoang and Antoncic, 2003). Numerous studies have suggested that entrepreneurial firms usually involved in a positive and comprehensive environmental glance and continuously face the challenge of new and external information (Yan et al, 2018;Yoon et al, 2018). Many studies anticipated that firms with high EO tend to have a chance to find potential partners (Figure 1).…”
Section: Literature Review Theory and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the break-down of traditional and hierarchical structures also talks about organizational-wide communications that enable the expansion of a shared revelation (Hoang and Antoncic, 2003). Numerous studies have suggested that entrepreneurial firms usually involved in a positive and comprehensive environmental glance and continuously face the challenge of new and external information (Yan et al, 2018;Yoon et al, 2018). Many studies anticipated that firms with high EO tend to have a chance to find potential partners (Figure 1).…”
Section: Literature Review Theory and Hypothesismentioning
confidence: 99%
“…Several researchers have proposed that born global firms developed the new market and new venture of business; they provide opportunities to increase the market success and knowledge (Autio, 2005;Cavusgil and Knight, 2009;Yan et al, 2018). Therefore hypothesize is of EO may be more strongly associated with performance when it is combined with high network capability.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Recent studies on the use of e-commerce and crowdfunding provide initial insights on the indirect effects of awareness and knowledge building through digital entrepreneurship platforms on career experimentation in the agriculture and farming sector. Both the findings by Su et al (2021) and Yan et al (2018) display that knowledge on e-commerce tools have an indirect effect on rural youths' engagement with farming (with new types of agricultural business entities) as a profession in rural China. Furthermore, two studies have also investigated the use of crowdfunding platforms for the agri-business sector.…”
Section: Community-based Digital Communication Tools Initiated By Dig...mentioning
confidence: 97%
“…Yan, Z. et al (2018) put forward the research in the field of online finance. From the theoretical perspective of social network behavior, entrepreneurial leaders may attract investors' attention through various social network behaviors [5]. As a new investment platform, grandstanding provides favorable and powerful opportunities for sustainable economic development.…”
Section: Internet Finance In the Information Agementioning
confidence: 99%